Quality of life before and after cosmetic surgery. (30th September 2013) - Bensoussan, Jean-Charles; Bolton, Michael A.; Pi, Sarah; Powell-Hicks, Allycin L.; Postolova, Anna; Razani, Bahram; Reyes, Kevin; IsHak, Waguih William
<x content-type="archive" xml:space="preserve">Abstract</x> This article reviews the literature regarding the impact of cosmetic surgery on health-related quality of life (QOL). Studies were identified through PubMed/Medline and PsycINFO searches from January 1960 to December 2011. Twenty-eight studies were included in this review, according to specific selection criteria. The procedures and tools employed in cosmetic surgery research studies were remarkably diverse, thus yielding difficulties with data analysis. However, data indicate that individuals undergoing cosmetic surgery began with lower values on aspects of QOL than control subjects, and experienced significant QOL improvement post-procedurally, an effect that appeared to plateau with time. Despite the complexity of measuring QOL in cosmetic surgery patients, most studies showed an improvement in QOL after cosmetic surgery procedures. However, this finding was clouded by measurement precision as well as heterogeneity of procedures and study populations. Future research needs to focus on refining measurement techniques, including developing cosmetic surgery–specific QOL measures.